Electrode active material, preparation method thereof and air battery

By providing a porous structure and first oxygen-containing group on the electrode active material of the lithium air battery, and doping nitrogen, transition metals and sulfur elements, the problem of poor conductivity of the electrode active material is solved, and the electrochemical performance and energy density of the battery are significantly improved.

CN119833654APending Publication Date: 2025-04-15CHONGQING CHANGAN AUTOMOBILE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510030220.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The oxygen involved in the electrode active material in lithium air batteries is slow in reaction kinetics and poor conductivity of the discharge product Li2O2, resulting in a large charge and discharge overpotential.

Method used

A porous material is used as the electrode active material, and a first oxygen-containing group is provided on its surface and pore surface to improve the conductivity and electrochemical properties of the electrode active material. The electrode active material forms rich catalytic active sites through doping of nitrogen, transition metal and sulfur elements, reducing reaction activation energy and increasing the rate of oxygen participating in the reaction.

Benefits of technology

It improves the conductivity and electrochemical properties of the electrode active material, reduces the charge and discharge overpotential, and improves the discharge specific capacity and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833654A_ABST
    Figure CN119833654A_ABST
Patent Text Reader

Abstract

The invention relates to the field of composite materials, in particular to the field of battery composite materials, and particularly relates to an electrode active material, a preparation method thereof and an air battery. The present disclosure provides an electrode active material, the electrode active material being a porous material, the electrode active material including a first oxygen-containing group. The first oxygen-containing group comprises a part arranged on the outer surface of the electrode active material and further comprises a part arranged on the hole surface of the electrode active material. The first oxygen-containing group is used for improving the electric activity of the electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of composite materials, in particular to the field of battery composite materials, and specifically to an electrode active material and a preparation method thereof, and an air battery. Background Art

[0002] As the global new energy vehicle market continues to heat up, power battery technology has become the focus of attention within and outside the industry. Although traditional lithium batteries have made significant progress, the bottleneck problem in energy density is becoming increasingly prominent, and they cannot meet the urgent demand for higher energy density in future high-end automobiles and electric aircraft.

[0003] Lithium-air batteries use lithium to react with oxygen in the air to release energy. They have the highest theoretical specific energy (3458Wh / kg) among rechargeable batteries. They are also environmentally friendly and safe, and are considered to be one of the most promising next-generation battery technologies. Electrode active materials are the most important factor affecting the performance of lithium-air batteries. In related technologies, electrode active materials have problems such as slow oxygen-involved reaction kinetics and poor conductivity of the discharge product Li2O2, which leads to large overpotentials in the charge and discharge of air batteries.

[0004] Therefore, an electrode active material and a preparation method thereof, and an air battery are expected to overcome at least one of the above problems. Summary of the invention

[0005] The present disclosure provides an electrode active material and a preparation method thereof, and an air battery, which are used to overcome at least one of the above problems. The technical solution of the present application is as follows:

[0006] In one aspect, an electrode active material is provided, wherein the electrode active material is a porous material, and the electrode active material includes a first oxygen-containing group. The first oxygen-containing group includes a portion disposed on the outer surface of the electrode active material and a portion disposed on the pore surface of the electrode active material. The first oxygen-containing group is used to enhance the electrical activity of the electrode active material.

[0007] In the present disclosure, the electrode active material is a porous material, which is conducive to the diffusion of oxygen and the adsorption of the intermediate product Li2O2, so that the conduction speed of oxygen and metal ions, such as lithium ions, inside the electrode active material can be increased, thereby improving the conductivity of the electrode active material. Moreover, when the electrode active material is a porous material, abundant Li2O2 formation and decomposition centers can be formed. In addition, by setting the electrode active material as a porous material, the first oxygen-containing group can be set on the pore surface, so that the distribution amount of the first oxygen-containing group in the electrode active material can be increased, the charge and discharge overpotential can be reduced, the effect of the first oxygen-containing group on improving the electroactivity of the electrode active material can be improved, and the electrochemical performance of the electrode active material can be improved, thereby improving the discharge specific capacity and rate performance of the battery using the electrode active material.

[0008] In a feasible embodiment, the polarity of the first oxygen-containing group is less than that of the carboxyl group.

[0009] In a feasible embodiment, the first oxygen-containing group includes at least one of a hydroxyl group, an ether group, a ketone group and a lactone group.

[0010] In a feasible embodiment, the electrode active material includes a second oxygen-containing group. The second oxygen-containing group includes a portion disposed on the outer surface of the electrode active material and a portion disposed on the pore surface of the electrode active material. The mass proportion of the second oxygen-containing group in the electrode active material is less than the mass proportion of the first oxygen-containing group in the electrode active material. The first oxygen-containing group can be formed by converting the second oxygen-containing group.

[0011] In a feasible embodiment, the electrode active material includes carbon, oxygen, sulfur, nitrogen and transition metal elements.

[0012] Carbon materials have advantages such as high conductivity and low cost, and transition metal elements can make up for their shortcomings of insufficient catalytic activity. At the same time, doping with heteroatoms such as transition metals, nitrogen, and sulfur can improve the electronic structure of electrode active materials and thus improve their electrochemical performance, and can also improve the surface state of electrode active materials, enhance the adsorption performance of reaction intermediates, make the reaction easier, and thus improve reversible catalytic performance.

[0013] In a feasible embodiment, the transition metal element includes at least one of nickel, cobalt, manganese, iron, chromium, titanium, vanadium, copper and zinc.

[0014] In a feasible embodiment, the chemical bonds of the electrode active material include at least one of: a chemical bond between a transition metal atom and a sulfur atom, a chemical bond between a transition metal atom and a nitrogen atom, a chemical bond between a carbon atom and a nitrogen atom, and a chemical bond between a carbon atom and a sulfur atom.

[0015] The electrode active material provided by the present disclosure is doped with nitrogen, transition metal and sulfur to form rich transition metal-sulfur, transition metal-nitrogen, carbon-nitrogen and carbon-sulfur catalytic active sites, which reduces the activation energy required for the reaction, that is, reduces the overpotential of charge and discharge, accelerates the generation and decomposition rate of Li2O2, and makes the reaction more complete. At the same time, the catalytic active sites can also adsorb intermediate products, reduce the energy required for the reaction, and thus accelerate the rate at which oxygen participates in the reaction.

[0016] On the other hand, an air battery is provided, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a conductive agent, a binder and the electrode active material as described above.

[0017] In a feasible embodiment, the first coulombic efficiency of the air battery is in the range of 60%-89%, and / or the 200-cycle capacity retention rate of the air battery is in the range of 60%-90%.

[0018] In a feasible embodiment, the discharge gram capacity of the air battery is greater than or equal to 1400 mAh per gram.

[0019] On the other hand, a method for preparing an electrode active material is provided, comprising: forming an electrode active material precursor; the electrode active material precursor is a porous material; forming a first oxygen-containing group on the outer surface of the electrode active material precursor and on the pore surface of the electrode active material precursor; the first oxygen-containing group is used to enhance the electrical activity of the electrode active material.

[0020] In a feasible embodiment, the forming of the first oxygen-containing group includes: oxidizing the electrode active material precursor to form a second oxygen-containing group on the outer surface of the electrode active material precursor and the pore surface of the electrode active material precursor; and microwave heating the oxidized electrode active material precursor to convert at least part of the second oxygen-containing group into the first oxygen-containing group.

[0021] In a feasible embodiment, the oxidant for oxidizing the electrode active material precursor is hydrogen peroxide; and the mass ratio of the electrode active material precursor to the hydrogen peroxide is in the range of 1:10-1:30.

[0022] In a feasible embodiment, during the microwave heating of the oxidized electrode active material precursor, the microwave power ranges from 400 watts to 2000 watts, and / or the microwave heating time of the oxidized electrode active material precursor ranges from 10 seconds to 120 seconds.

[0023] In a feasible embodiment, the formation of the electrode active material precursor includes: dissolving a carbon source and a nitrogen source in an acidic solution to obtain a first solution; adding a transition metal source and a sulfur source to the first solution to perform a hydrothermal reaction to obtain a first precipitate; and calcining the first precipitate under an inert gas atmosphere to obtain the electrode active material precursor.

[0024] In a feasible embodiment, the carbon source and the nitrogen source are biomass materials; the acidic solution includes at least one of sulfuric acid solution, hydrochloric acid solution, nitric acid solution and acetic acid solution; and the concentration range of the acidic solution is 0.5%-15%.

[0025] In a feasible embodiment, the sulfur source includes at least one of thiourea and ammonium thioacetate; and the mass ratio of the biomass material to the sulfur source is in the range of 1:0.01-1:5.

[0026] In a feasible embodiment, the biomass material includes at least one of wheat straw, rice straw, corn straw, wood chips, peanut shells, coconut shells, corn cobs, wheat bran, rice husks and coffee grounds.

[0027] In a feasible embodiment, the transition metal source is a transition metal sulfate; the mass ratio of the biomass material to the transition metal sulfate is in the range of 1:0.001-1:8.

[0028] In a feasible embodiment, the calcination temperature of the first precipitate is in the range of 600 degrees Celsius to 1200 degrees Celsius; and / or the calcination time of the first precipitate is in the range of 4 hours to 8 hours.

[0029] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the specification are used to explain the principles of the present application, and do not constitute an improper limitation on the present application.

[0031] Figure 1 A diagram of a method for preparing an electrode active material according to an embodiment of the present disclosure;

[0032] Figure 2 A diagram of another method for preparing an electrode active material according to an embodiment of the present disclosure;

[0033] Figure 3 is a SEM image of an electrode active material provided according to an embodiment of the present disclosure;

[0034] Figure 4The first cycle charge and discharge curve of the air battery made of the electrode active material provided in the embodiment of the present disclosure;

[0035] Figure 5 This is an AC impedance diagram of an air battery made from the electrode active material provided in an embodiment of the present disclosure. DETAILED DESCRIPTION

[0036] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.

[0037] Unless the context requires otherwise, throughout the specification and claims, the term "including" is to be interpreted as an open, inclusive meaning, that is, "including, but not limited to". In the description of the specification, the terms "one embodiment", "some embodiments", "exemplary embodiments", "examples" or "some examples" and the like are intended to indicate that specific features, structures, materials or characteristics associated with the embodiment or example are included in at least one embodiment or example of the present disclosure. The schematic representations of the above terms do not necessarily refer to the same embodiment or example. In addition, the specific features, structures, materials or characteristics described may be included in any one or more embodiments or examples in any appropriate manner.

[0038] In the following, the terms "first" and "second" are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the embodiments of the present disclosure, unless otherwise specified, "plurality" means two or more.

[0039] “At least one of A, B, and C” has the same meaning as “at least one of A, B, or C” and both include the following combinations of A, B, and C: A only, B only, C only, the combination of A and B, the combination of A and C, the combination of B and C, and the combination of A, B, and C.

[0040] “A and / or B” includes the following three combinations: A only, B only, and a combination of A and B.

[0041] Exemplary embodiments are described herein with reference to cross-sectional views and / or plan views that are idealized exemplary drawings. In the drawings, the thickness of the layers and / or the area of ​​the regions are exaggerated for clarity. Therefore, variations in the shapes relative to the drawings due to, for example, manufacturing techniques and / or tolerances are conceivable. Therefore, the exemplary embodiments should not be interpreted as being limited to the shapes of the regions shown herein, but include shape deviations due to, for example, manufacturing. Therefore, the regions shown in the drawings are schematic in nature, and their shapes and proportions are not intended to illustrate the actual shapes of the regions of the device, and are not intended to limit the scope of the exemplary embodiments.

[0042] According to some embodiments of the present disclosure, an electrode active material is provided, the electrode active material is a porous material, the electrode active material includes a first oxygen-containing group, at least part of the first oxygen-containing group is disposed on the outer surface of the electrode active material, and / or at least part of the first oxygen-containing group is also disposed on the pore surface of the electrode active material. In the present disclosure, the first oxygen-containing group is used to enhance the electrical activity of the electrode active material.

[0043] In the present disclosure, the electrode active material is a porous material, which is conducive to the diffusion of oxygen and the adsorption of the intermediate product Li2O2, so that the conduction speed of oxygen and metal ions, such as lithium ions, inside the electrode active material can be increased, thereby improving the catalytic efficiency of the electrode active material. Moreover, when the electrode active material is a porous material, abundant Li2O2 formation and decomposition centers can be formed, which can reduce the charge and discharge overpotential. In addition, by setting the electrode active material as a porous material, the first oxygen-containing group can be set on the pore surface, so that the distribution amount of the first oxygen-containing group in the electrode active material can be increased, the effect of the first oxygen-containing group on improving the electroactivity of the electrode active material can be improved, and the electrochemical performance of the electrode active material can be improved, thereby improving the discharge specific capacity and rate performance of the battery using the electrode active material.

[0044] In some possible embodiments, the polarity of the first oxygen-containing group is less than the polarity of the carboxyl group.

[0045] Exemplarily, the first oxygen-containing group includes at least one of a hydroxyl group, an ether group, a ketone group, and a lactone group.

[0046] The above groups have the advantages of low polarity and high electroactivity. First, they can avoid side reactions between the first oxygen-containing group and materials such as electrolytes; second, they can enhance the effect of the first oxygen-containing group in enhancing the electroactivity of electrode active materials.

[0047] In some feasible embodiments, the electrode active material includes a second oxygen-containing group, at least part of the second oxygen-containing group is disposed on the outer surface of the electrode active material, and / or at least part of the second oxygen-containing group is disposed on the pore surface of the electrode active material. The mass proportion of the second oxygen-containing group in the electrode active material is less than the mass proportion of the first oxygen-containing group in the electrode active material, and the first oxygen-containing group can be formed by converting the second oxygen-containing group.

[0048] Through the above arrangement, the first oxygen-containing group can be formed by utilizing the conversion reaction of the second oxygen-containing group, which can simplify the process of forming the first oxygen-containing group.

[0049] Illustratively, the second oxygen-containing group includes at least one of a carboxyl group, a hydroxyl group, and a keto group.

[0050] When the second oxygen-containing group includes at least one of a carboxyl group and a lactone group, when the second oxygen-containing group on the surface of the electrode active material is converted into the first oxygen-containing group, the carboxyl group and other high polarity, poor pseudocapacitance groups can be converted into ether groups and / or ketone groups and other low polarity, high electroactive groups, which can greatly improve the electrochemical properties of the electrode active material.

[0051] In some feasible embodiments, the electrode active material includes carbon, oxygen, sulfur, nitrogen and transition metal elements.

[0052] Carbon materials have advantages such as high conductivity and low cost, and transition metal elements can make up for their shortcomings of insufficient catalytic activity. At the same time, doping with heteroatoms such as transition metals, nitrogen, and sulfur can improve the electronic structure of electrode active materials and thus improve their electrochemical performance, and can also improve the surface state of electrode active materials, enhance the adsorption performance of reaction intermediates, make the reaction easier, and thus improve reversible catalytic performance.

[0053] Exemplarily, the transition metal element includes at least one of nickel (Ni), cobalt (Co), manganese (Mn), iron (Fe), chromium (Cr), titanium (Ti), vanadium (V), copper (Cu), and zinc (Zn).

[0054] In some feasible embodiments, the chemical bonds of the electrode active material include at least one of a chemical bond between a transition metal atom and a sulfur atom, a chemical bond between a transition metal atom and a nitrogen atom, a chemical bond between a carbon atom and a nitrogen atom, and a chemical bond between a carbon atom and a sulfur atom.

[0055] The electrode active material provided by the present disclosure is doped with nitrogen, transition metal and sulfur to form rich transition metal-sulfur, transition metal-nitrogen, carbon-nitrogen and carbon-sulfur catalytic active sites, which reduces the activation energy required for the reaction, that is, reduces the overpotential of charge and discharge, accelerates the generation and decomposition rate of Li2O2, and makes the reaction more complete. At the same time, the catalytic active sites can also adsorb intermediate products, reduce the energy required for the reaction, and thus accelerate the rate at which oxygen participates in the reaction.

[0056] According to some embodiments of the present disclosure, an air battery is also provided. The air battery can be selected from any one of a lithium-air battery, an aluminum-air battery or a zinc-air battery. In the present disclosure, a lithium-air battery is taken as an example for description.

[0057] When the air battery is selected from a non-aqueous liquid lithium-air battery, the air battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte. Exemplarily, the positive electrode sheet comprises a conductive agent, a binder and the electrode active material disclosed above.

[0058] Exemplarily, the electrode active material is mixed evenly with the conductive agent and the adhesive in a certain proportion, N-methylpyrrolidone (NMP) is added as a diluent, and stirred to form a uniform slurry. The slurry is applied to the current collector, vacuum dried and cut into discs, the diameter of the discs is, for example, 14 mm. The disc is used as the positive electrode, the metal lithium sheet is used as the negative electrode, a commercial glass fiber membrane is selected as the diaphragm, and 1 mol / L tetraethylene glycol dimethyl ether / bistrifluoromethanesulfonyl imide lithium (TEGDME / LiTFSI) is used as the electrolyte, and the lithium-air battery is assembled in a glove box filled with argon.

[0059] In some feasible embodiments, hexamethyldisilazane is dissolved in the electrolyte with a concentration of 0.1 mol / L.

[0060] The air battery was placed under high-purity oxygen conditions for charge and discharge testing, and the electrochemical window was measured to be 2V-4.5V.

[0061] In some feasible embodiments, the ratio of the electrode active material, the conductive agent and the binder is (8-9): (0.5-1): (0.5-1).

[0062] In the air battery, the positive electrode is selected from the disc, the negative electrode is selected from the metal lithium sheet, and the electrolyte is selected from 1 mol / L tetraethylene glycol dimethyl ether / lithium bis(trifluoromethanesulfonyl)imide (TEGDME / LiTFSI).

[0063] Exemplarily, the conductive agent is used to improve the conductivity of the positive electrode, and can be selected from at least one of carbon black, acetylene black or Ketjen black. The binder is used to adhere the electrode active material and the conductive agent to the current collector of the pole piece, and can be selected from at least one of polyvinylidene fluoride, polytetrafluoroethylene or sodium carboxymethyl cellulose. The current collector can be selected from any one of carbon paper or nickel mesh.

[0064] In some feasible embodiments, the air battery is selected from a solid-state lithium-air battery, and the electrolyte can be selected from at least one of a sulfide electrolyte, an oxide electrolyte, and a polymer electrolyte. Exemplarily, during the assembly process of the positive electrode, the negative electrode, and the electrolyte, a Swagelok mold is used to apply pressure to improve the contact between the electrode and the electrolyte.

[0065] In some feasible embodiments, the sulfide electrolyte may be selected from any one of lithium germanium phosphorus sulfur LGPS, lithium phosphorus sulfur LPS or lithium phosphorus sulfur chlorine LPSCl. The oxide electrolyte is selected from any one of lithium lanthanum zirconium oxide LLZO, lithium lanthanum titanium oxide LLTO, and lithium phosphorus oxide nitrogen LiPON. The polymer electrolyte is selected from any one of polyethylene oxide PEO, polyacrylonitrile PAN, polymethyl methacrylate PMMA, and polyvinylidene fluoride PVDF. The applied pressure may be 80MPa-500MPa. Exemplarily, the applied pressure may be 80MPa, 100MPa, 200MPa, 300MPa, 400MPa, 460MPa or 500MPa, etc.

[0066] According to some embodiments of the present disclosure, a method for preparing an electrode active material is also provided. Figure 1 and Figure 2 As shown, Figure 1 A diagram of a method for preparing an electrode active material according to an embodiment of the present disclosure is shown. Figure 2 This is a diagram of another method for preparing an electrode active material according to an embodiment of the present disclosure, wherein the method comprises step S10 and step S20.

[0067] In step S10, an electrode active material precursor is formed; the electrode active material precursor is a porous material. Step S10, for example, includes steps S11 to S13.

[0068] In step S11, a carbon source and a nitrogen source are dissolved in an acidic solution to obtain a first solution.

[0069] In some feasible embodiments, the carbon source and the nitrogen source are biomass materials, and the biomass materials include amino groups. Exemplarily, the biomass materials can be selected from wheat straw, rice straw, corn straw, wood chips, peanut shells, coconut shells, corn cobs, wheat bran, rice husks or coffee grounds. Using cheap and readily available biomass materials as carbon sources and nitrogen sources can effectively reduce production costs.

[0070] The acidic solution includes at least one of a sulfuric acid solution, a hydrochloric acid solution, a nitric acid solution and an acetic acid solution; the concentration of the acidic solution ranges from 0.5% to 15%. For example, the concentration of the acidic solution can be 0.5%, 3%, 5%, 7%, 9%, 11%, 13% or 15%, etc.

[0071] Treating biomass materials with acid can make them porous, increase the surface area of ​​electrode active materials and expose more catalytic active sites, provide more channels and / or spaces for the accumulation of discharge products, and deposit more Li2O2, thereby improving the interfacial mass transfer efficiency of reactions and products. At the same time, the porous structure is also conducive to the diffusion of oxygen and the adsorption of the intermediate product Li2O2, which can increase the conduction speed of oxygen and metal ions, such as lithium ions, inside the electrode active materials, thereby improving the conductivity of the electrode active materials.

[0072] In some feasible embodiments, after the carbon source and the nitrogen source are dissolved in the acidic solution, heating and stirring operations are performed. The heating temperature can be 40 degrees Celsius to 80 degrees Celsius, and the stirring time can be 4 hours to 24 hours.

[0073] For example, the heating temperature can be 40 degrees Celsius, 50 degrees Celsius, 60 degrees Celsius, 70 degrees Celsius or 80 degrees Celsius, etc.; the stirring time can be 4 hours, 8 hours, 12 hours, 16 hours, 20 hours or 24 hours, etc.

[0074] In some feasible embodiments, the heating temperature may be 60 degrees Celsius to 80 degrees Celsius, and the heating time may be 12 hours.

[0075] In step S12, a transition metal source and a sulfur source are added to the first solution to perform a hydrothermal reaction to obtain a first precipitate.

[0076] In some feasible embodiments, the sulfur source includes at least one of thiourea and ammonium thioacetate. The mass ratio of the biomass material to the sulfur source ranges from 1:0.01 to 1:5.

[0077] Exemplarily, the mass ratio of the biomass material to the sulfur source ranges from 1:0.01 to 1:3.

[0078] Exemplarily, the mass ratio of the biomass material to the sulfur source can be 1:0.01, 1:0.05, 1:0.1, 1:0.5, 1:1 or 1:5.

[0079] In some feasible embodiments, the transition metal source is a transition metal sulfate, and the mass ratio of the biomass material to the transition metal sulfate is in the range of 1:0.001-1:8.

[0080] Exemplarily, the mass ratio of the biomass material to the transition metal sulfate is in the range of 1:0.001-1:5.

[0081] Illustratively, the mass ratio of the biomass material to the transition metal sulfate can be 1:0.001, 1:0.008, 1:0.01, 1:0.08, 1:0.1, 1:0.8, 1:1 or 1:8, etc.

[0082] In some feasible embodiments, the temperature of the hydrothermal reaction can be 100 degrees Celsius to 220 degrees Celsius, and the insulation time can be 6 hours to 15 hours.

[0083] For example, the temperature of the hydrothermal reaction can be 100 degrees Celsius, 120 degrees Celsius, 140 degrees Celsius, 160 degrees Celsius, 180 degrees Celsius, 200 degrees Celsius or 220 degrees Celsius, etc.; the insulation time can be 6 hours, 9 hours, 12 hours or 15 hours, etc.

[0084] In some feasible embodiments, the temperature of the hydrothermal reaction may be 180 degrees Celsius, and the insulation time may be 12 hours.

[0085] By utilizing the amino groups of biomass materials, combined with transition metals provided by transition metal sulfates and sulfur elements provided by sulfur sources, abundant transition metal-sulfur, transition metal-nitrogen, carbon-nitrogen, and carbon-sulfur catalytic active sites are formed, which reduces the activation energy required for the reaction, that is, reduces the overpotential of charge and discharge, accelerates the production and decomposition of Li2O2, and makes the reaction more complete.

[0086] In some feasible embodiments, step S12 further includes washing the first precipitate with deionized water and vacuum drying to remove impurities such as reaction by-products.

[0087] In some feasible embodiments, the vacuum drying temperature may be 60 degrees Celsius, and the vacuum drying time may be 6 hours to 18 hours.

[0088] For example, the vacuum drying time can be 6 hours, 9 hours, 12 hours, 15 hours or 18 hours, etc.

[0089] In some feasible embodiments, the vacuum drying time may be 60 degrees Celsius, and the vacuum drying time may be 12 hours.

[0090] In step S13, the first precipitate is calcined at high temperature in an inert gas atmosphere to obtain an electrode active material precursor.

[0091] High temperature carbonization of the first precipitate can be achieved through high temperature calcination.

[0092] In some feasible embodiments, the calcination temperature of the first precipitate is in the range of 600 degrees Celsius to 1200 degrees Celsius; and / or the calcination time of the first precipitate is in the range of 4 hours to 8 hours.

[0093] For example, the calcination temperature of the first precipitate may be 600 degrees Celsius, 700 degrees Celsius, 800 degrees Celsius, 900 degrees Celsius, 1000 degrees Celsius, 1100 degrees Celsius, or 1200 degrees Celsius, etc.

[0094] For example, the calcination time of the first precipitate can be 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, etc.

[0095] Exemplarily, the inert gas may be nitrogen or argon, etc. Exemplarily, the inert gas is selected from nitrogen.

[0096] In some feasible embodiments, the calcination temperature rise rate may be 2 degrees Celsius per minute to 10 degrees Celsius per minute.

[0097] Exemplarily, the inert gas is nitrogen, and the calcination heating rate can be 2 degrees Celsius per minute, 4 degrees Celsius per minute, 5 degrees Celsius per minute, 6 degrees Celsius per minute, 8 degrees Celsius per minute, or 10 degrees Celsius per minute, etc.

[0098] In some feasible embodiments, step S13 further comprises: grinding the dried first precipitate obtained in step S12, wherein the grinding step is performed before calcination.

[0099] In some feasible embodiments, step S13 further includes: acid washing the electrode active material precursor, and the acid washing step is performed after calcination.

[0100] The pickling solution is, for example, selected from hydrochloric acid or sulfuric acid, the concentration of the acid solution is 0.5 mol / L to 1 mol / L, and the pickling time is, for example, selected from 6 hours to 10 hours.

[0101] Exemplarily, the concentration of the acid solution can be 0.5 mol / L, 0.7 mol / L, 0.9 mol / L or 1 mol / L, etc.; the pickling time can be 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, etc.

[0102] In step S20, first oxygen-containing groups are formed on the outer surface of the electrode active material precursor and the pore surface of the electrode active material precursor; the first oxygen-containing groups are used to enhance the electrical activity of the electrode active material.

[0103] In some feasible embodiments, step S20 includes step S21 and step S22.

[0104] In step S21 , the electrode active material precursor is oxidized to form second oxygen-containing groups on the outer surface of the electrode active material precursor and the pore surfaces of the electrode active material precursor.

[0105] Specifically, the electrode active material precursor is mixed with an oxidant solution for oxidizing the electrode active material precursor, heated and stirred, rinsed with deionized water and vacuum dried.

[0106] In some feasible embodiments, the oxidant for oxidizing the electrode active material precursor can be selected from hydrogen peroxide, and the mass ratio of the electrode active material precursor to hydrogen peroxide ranges from 1:10 to 1:30. Exemplarily, the mass ratio of the electrode active material precursor to hydrogen peroxide can be 1:10, 1:15, 1:20, 1:25 or 1:30, etc.

[0107] In some feasible embodiments, the heating temperature may be 60 degrees Celsius to 100 degrees Celsius, and the holding time may be 0.5 hours to 2 hours. For example, the heating temperature may be 60 degrees Celsius, 70 degrees Celsius, 80 degrees Celsius, 90 degrees Celsius or 100 degrees Celsius, etc.; the holding time may be 0.5 hours, 1 hour, 1.5 hours or 2 hours, etc.

[0108] In some feasible embodiments, the drying time can be 6 hours to 18 hours. Exemplarily, the drying time can be 6 hours, 8 hours, 12 hours, 14 hours or 18 hours, etc.

[0109] In step S22 , the oxidized electrode active material precursor is heated by microwaves to convert at least a portion of the second oxygen-containing groups into first oxygen-containing groups.

[0110] In some feasible embodiments, during microwave heating of the oxidized electrode active material precursor, the microwave power ranges from 400 watts to 2000 watts; and / or the microwave heating time of the oxidized electrode active material precursor ranges from 10 seconds to 120 seconds.

[0111] The microwave power may be 400 watts, 600 watts, 800 watts, 1000 watts, 1200 watts, 1400 watts, 1600 watts, 1800 watts, or 2000 watts, etc.

[0112] In some possible embodiments, the microwave power may range from 400 watts to 1200 watts.

[0113] Exemplarily, the microwave heating time can be 10 seconds, 30 seconds, 50 seconds, 60 seconds, 70 seconds, 90 seconds or 120 seconds, etc.

[0114] The following are examples of the method for preparing an electrode active material according to the above content, and comparative examples of the method for preparing an electrode active material according to related art.

[0115] Example 1

[0116] 1. Wash, dry and crush 2g corn cobs, disperse them in 3% (wt%) acetic acid solution, heat to 60°C and stir for 12h. Then add 0.6g nickel sulfate heptahydrate and 1g thiourea and stir for 2h. Hydrothermally react the above solution at 180°C for 12h. After the hydrothermal autoclave is completely cooled, centrifuge and wash until the washing liquid is neutral, and dry at 60°C for 12h to obtain the first precipitate.

[0117] 2. Grind the first precipitate thoroughly, and calcine it at 800°C for 6 hours in a tube furnace in an inert atmosphere, such as a nitrogen atmosphere, with a heating rate of 5°C / min. Cool it naturally to room temperature in the furnace, dissolve it in 1 mol / L hydrochloric acid, stir and wash it for 8 hours to remove impurities, wash it with deionized water until the washing liquid is neutral, and vacuum dry it at 80°C for 8 hours to obtain an electrode active material precursor.

[0118] 3. Grind the electrode active material precursor into powder, mix it with hydrogen peroxide solution, the mass ratio of electrode active material precursor to hydrogen peroxide solution is 1:20, and stir at 80℃ for 1h. After the solution cools down, wash the first precipitate with deionized water until the washing liquid is neutral, and vacuum dry it at 80℃ for 8h. Put the oxidized electrode active material precursor into a microwave oven and heat it at 600W for 60s to obtain Figure 3 The electrode active material shown, Figure 3 The SEM image of the electrode active material provided according to the embodiment of the present disclosure is shown in Figure 1. The electrode active material is made of corn cob as raw material and doped with transition metal, nitrogen and sulfur.

[0119] In Example 1, corn cobs were used as the biochar source, and the mass ratio of biochar: sulfur-containing organic matter: metal salt was 1:0.5:0.3.

[0120] Example 2

[0121] 1. Wash, dry and crush 2g of wheat straw, disperse it in 3% (wt%) acetic acid solution, heat it to 60°C and stir it for 12h. Then add 0.6g of nickel sulfate heptahydrate and 1g of thiourea, stir it for 2h, and hydrothermally react the above solution at 180°C for 12h. After the hydrothermal autoclave is completely cooled, centrifuge and wash until the washing liquid is neutral, and dry it at 60°C for 12h to obtain the first precipitate.

[0122] 2. Grind the first precipitate thoroughly, and calcine it at 800°C for 6 hours in a tube furnace in an inert atmosphere, such as nitrogen atmosphere, with a heating rate of 5°C / min. Cool it naturally to room temperature in the furnace, dissolve it in 1 mol / L hydrochloric acid, stir and wash it for 8 hours to remove impurities, wash it with deionized water until the washing liquid is neutral, and vacuum dry it at 80°C for 8 hours.

[0123] 3. Grind the electrode active material precursor into powder, mix it with hydrogen peroxide solution, the mass ratio of electrode active material precursor to hydrogen peroxide solution is 1:20, and stir at 80°C for 1h. After the solution is cooled, wash the first precipitate with deionized water until the washing liquid is neutral, and vacuum dry it at 80°C for 8h. Put the oxidized electrode active material precursor into a microwave oven and heat it at 600W for 60s to obtain an electrode active material. The electrode active material uses wheat straw as a raw material and is doped with transition metals, nitrogen and sulfur.

[0124] Example 3

[0125] 1. Wash, dry and crush 2g corn cobs, disperse them in 3% (wt%) acetic acid solution, heat to 60°C and stir for 12h. Then add 0.6g nickel sulfate heptahydrate and 1.6g thioacetamide, stir for 2h, and hydrothermally react the solution at 180°C for 12h. After the hydrothermal autoclave is completely cooled, centrifuge and wash until the washing liquid is neutral, and dry at 60°C for 12h to obtain the first precipitate.

[0126] 2. Grind the first precipitate thoroughly, and calcine it at 800°C for 6 hours in a tube furnace in an inert atmosphere, such as a nitrogen atmosphere, with a heating rate of 5°C / min. Cool it naturally to room temperature in the furnace, dissolve it in 1 mol / L hydrochloric acid, stir and wash it for 8 hours to remove impurities, wash it with deionized water until the washing liquid is neutral, and vacuum dry it at 80°C for 8 hours.

[0127] 3. Grind the electrode active material precursor into powder, mix it with hydrogen peroxide solution, the mass ratio of electrode active material precursor to hydrogen peroxide solution is 1:20, and stir at 80°C for 1h. After the solution is cooled, wash the first precipitate with deionized water until the washing liquid is neutral, and vacuum dry it at 80°C for 8h. Put the oxidized electrode active material precursor into a microwave oven and heat it at 600W for 60s to obtain an electrode active material. The electrode active material uses corn cobs as raw materials and is doped with transition metals, nitrogen and sulfur.

[0128] In Example 3, the sulfur-containing organic matter is selected from thioacetamide, and the mass ratio of biochar to the sulfur-containing organic matter is adjusted.

[0129] Example 4

[0130] 1. Wash, dry and crush 2g corn cobs, disperse them in 3% (wt%) acetic acid solution, heat to 60°C and stir for 12h. Then add 0.4g cobalt sulfate heptahydrate and 1g thiourea, stir for 2h, and hydrothermally react the above solution at 180°C for 12h. After the hydrothermal autoclave is completely cooled, centrifuge and wash until the washing liquid is neutral, and dry at 60°C for 12h to obtain the first precipitate.

[0131] 2. Grind the first precipitate thoroughly, and calcine it at 800°C for 6 hours in a tube furnace in an inert atmosphere, such as a nitrogen atmosphere, with a heating rate of 5°C / min. Cool it naturally to room temperature in the furnace, dissolve it in 1 mol / L hydrochloric acid, stir and wash it for 8 hours to remove impurities, wash it with deionized water until the washing liquid is neutral, and vacuum dry it at 80°C for 8 hours.

[0132] 3. Grind the electrode active material precursor into powder, mix it with hydrogen peroxide solution, the mass ratio of electrode active material precursor to hydrogen peroxide solution is 1:20, and stir at 80°C for 1h. After the solution is cooled, wash the solid with deionized water until the washing liquid is neutral, and vacuum dry it at 80°C for 8h. Put the oxidized electrode active material precursor into a microwave oven and heat it at 600W for 60s to obtain the electrode active material, which uses corn cobs as raw materials and is doped with transition metals, nitrogen and sulfur.

[0133] In Example 4, the doped transition metal is changed from nickel to cobalt, and the mass ratio of biochar and transition metal salt is adjusted.

[0134] Example 5

[0135] 1. Wash, dry and crush 2g corn cobs, disperse them in 3% (wt%) acetic acid solution, heat to 60°C and stir for 12h. Then add 0.6g nickel sulfate heptahydrate and 1g thiourea and stir for 2h. Hydrothermally react the above solution at 180°C for 12h. After the hydrothermal autoclave is completely cooled, centrifuge and wash until the washing liquid is neutral, and dry at 60°C for 12h to obtain the first precipitate.

[0136] 2. Grind the first precipitate thoroughly, and calcine it at 1000°C for 6 hours in a tube furnace in an inert atmosphere, such as a nitrogen atmosphere, with a heating rate of 5°C / min. Cool it naturally to room temperature in the furnace, dissolve it in 1 mol / L hydrochloric acid, stir and wash it for 8 hours to remove impurities, wash it with deionized water until the washing liquid is neutral, and vacuum dry it at 80°C for 8 hours.

[0137] 3. Grind the electrode active material precursor into powder, mix it with hydrogen peroxide solution, the mass ratio of electrode active material precursor to hydrogen peroxide solution is 1:20, and stir at 80°C for 1h. After the solution is cooled, wash the first precipitate with deionized water until the washing liquid is neutral, and vacuum dry it at 80°C for 8h. Put the oxidized electrode active material precursor into a microwave oven and heat it at 600W for 60s to obtain an electrode active material. The electrode active material uses corn cobs as raw materials and is doped with transition metals, nitrogen and sulfur.

[0138] Example 6

[0139] 1. Wash, dry and crush 2g corn cobs, disperse them in 3% (wt%) acetic acid solution, heat to 60°C and stir for 12h. Then add 0.6g nickel sulfate heptahydrate and 1g thiourea and stir for 2h. Hydrothermally react the above solution at 180°C for 12h. After the hydrothermal autoclave is completely cooled, centrifuge and wash until the washing liquid is neutral, and dry at 60°C for 12h to obtain the first precipitate.

[0140] 2. Grind the first precipitate thoroughly, and calcine it at 1000°C for 6 hours in a tube furnace in an inert atmosphere, such as a nitrogen atmosphere, with a heating rate of 5°C / min. Cool it naturally to room temperature in the furnace, dissolve it in 1 mol / L hydrochloric acid, stir and wash it for 8 hours to remove impurities, wash it with deionized water until the washing liquid is neutral, and vacuum dry it at 80°C for 8 hours.

[0141] 3. Grind the electrode active material precursor into powder, mix it with hydrogen peroxide solution, the mass ratio of electrode active material precursor to hydrogen peroxide solution is 1:20, and stir at 80°C for 1h. After the solution is cooled, wash the first precipitate with deionized water until the washing liquid is neutral, and vacuum dry it at 80°C for 8h. Put the oxidized electrode active material precursor into a microwave oven and heat it at 800W for 60s to obtain an electrode active material. The electrode active material uses corn cobs as raw materials and is doped with transition metals, nitrogen and sulfur.

[0142] Comparative Example 1

[0143] Wash, dry, and crush 2g corn cobs, disperse them in a 3% (wt%) acetic acid solution, and stir for 4h. Hydrothermally react the solution at 180℃ for 12h. After the hydrothermal autoclave is completely cooled, centrifuge and wash until the washing liquid is neutral, and dry at 60℃ for 12h to obtain the precursor material.

[0144] The precursor material is fully ground, and calcined at 1000°C for 6 hours in a tube furnace under an inert atmosphere, such as a nitrogen atmosphere, with a heating rate of 5°C / min. The electrode active material is obtained by naturally cooling the furnace to room temperature.

[0145] Comparative Example 2

[0146] Wash, dry, and crush 2g corn cobs, disperse them in a 3% (wt%) acetic acid solution, heat to 60°C, and stir for 12h. Then add 0.6g nickel sulfate heptahydrate and 1g thiourea, and stir for 2h. Hydrothermally react the above solution at 180°C for 12h. After the hydrothermal autoclave is completely cooled, centrifuge and wash until the washing liquid is neutral, and dry at 60°C for 12h. A composite material precursor is obtained.

[0147] The composite precursor is fully ground and calcined at 800°C for 6 hours in a tube furnace in an inert atmosphere, such as a nitrogen atmosphere, and the heating rate can be 5°C / min. It is naturally cooled to room temperature in the furnace, dissolved in 1 mol / L hydrochloric acid, stirred and washed for 8 hours to remove impurities, washed with deionized water until the washing liquid is neutral, and vacuum dried at 80°C for 8 hours. The electrode active material can be obtained, and the electrode active material is doped with transition metals, sulfur, and nitrogen.

[0148] According to Examples 1 to 6, the preparation method of the electrode active material of the embodiments of the present disclosure is simple, does not require complex process equipment, and has the advantages of low production cost and no generation of toxic and harmful substances during the production process.

[0149] Air batteries were prepared using the electrode active materials of Examples 1 to 6, Comparative Examples 1 and 2, and the first coulombic efficiency and 200-cycle capacity retention rate of the air batteries were tested to obtain the data shown in Table 1.

[0150] Table 1 First coulombic efficiency and 200-cycle capacity retention rate of air batteries

[0151] Serial number First coulombic efficiency 200 cycles capacity retention rate Example 1 88.7% 89.1% Example 2 85.9% 84.9% Example 3 82.6% 84.3% Example 4 85.3% 85.0% Example 5 80.5% 83.3% Example 6 84.7% 86.7% Comparative Example 1 67.7% 68.4% Comparative Example 2 70.5% 71.3%

[0152] The air battery made of the electrode active materials of Examples 1 to 6 has a first coulombic efficiency of 80%-89%, which is significantly greater than 67.7% of Comparative Example 1 and 70.5% of Comparative Example 2. The air battery made of the electrode active materials of Examples 1 to 6 has a 200-cycle capacity retention rate of 83%-90%, which is much greater than 68.4% of Comparative Example 1 and 71.3% of Comparative Example 2. It should be understood that Table 1 only shows the first coulombic efficiency and 200-cycle capacity retention rate of some embodiments. In other measured embodiments, the first coulombic efficiency can be between 60%-89%, and the 200-cycle capacity retention rate can be between 60%-90%.

[0153] In some possible embodiments, see Figure 4 , Figure 4 The first cycle charge and discharge curve of the air battery made of the electrode active material provided in the embodiment of the present disclosure is shown in FIG. 1 for comparison. Figure 4The first cycle charge and discharge curve of the air battery made of the electrode active material provided in the comparative example of the related technology is also included. Figure 4 In the figure, the horizontal axis is capacity in mAh / g, and the vertical axis is voltage in V. The dotted line is the reference value, i.e., the open circuit voltage value of the air battery. The charging curve of the air battery is above the dotted line, and the discharge curve of the air battery is below the dotted line. Figure 4 It can be seen that the discharge capacity of the air battery prepared using the electrode active material provided in Example 1 is about 2700 mAh / g, which is greater than the discharge capacity of 2350 mAh / g of the air battery prepared using the electrode active material provided in Comparative Example 1, and greater than the discharge capacity of 1800 mAh / g of the air battery prepared using the electrode active material provided in Comparative Example 2. It should be understood that in other measured embodiments, the discharge gram capacity of the air battery may be greater than or equal to 1400 mAh / g, for example, 1400 mAh / g, 1600 mAh / g, 2350 mAh / g or 2700 mAh / g, etc.

[0154] In some possible embodiments, see Figure 5 , Figure 5 The AC impedance diagram of the air battery made of the electrode active material provided in the embodiment of the present disclosure is shown in FIG. 1 for comparison. Figure 5 Also included is the AC impedance curve of the air battery made from the electrode active material provided in the comparative example of the related art. Figure 5 In the figure, the abscissa is the real part Z' of the AC impedance, in Ω, and the ordinate is the imaginary part -Z", in Ω. It can be seen from the figure that the total AC impedance of the air battery prepared using the electrode active material provided in Example 1 is 270Ω, the total AC impedance of the air battery prepared using the electrode active material provided in Example 3 is 310Ω, the total AC impedance of the air battery prepared using the electrode active material provided in Comparative Example 1 is 350Ω, and the total AC impedance of the air battery prepared using the electrode active material provided in Comparative Example 2 is 360Ω.

[0155] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto, and any changes or substitutions within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. An electrode active material, characterized in that The electrode active material is a porous material, and the electrode active material comprises: The first oxygen-containing group includes a portion disposed on the outer surface of the electrode active material and a portion disposed on the pore surface of the electrode active material; the first oxygen-containing group is used to enhance the electrical activity of the electrode active material.

2. The electrode active material according to claim 1, characterized in that The polarity of the first oxygen-containing group is less than that of the carboxyl group.

3. The electrode active material according to claim 1, characterized in that The first oxygen-containing group includes at least one of a hydroxyl group, an ether group, a keto group, and a lactone group.

4. The electrode active material according to claim 1, characterized in that The electrode active material comprises: The second oxygen-containing group includes a portion disposed on the outer surface of the electrode active material and a portion disposed on the pore surface of the electrode active material; The mass proportion of the second oxygen-containing group in the electrode active material is less than the mass proportion of the first oxygen-containing group in the electrode active material; and the first oxygen-containing group can be formed by converting the second oxygen-containing group.

5. The electrode active material according to any one of claims 1 to 4, characterized in that The electrode active material includes carbon element, oxygen element, sulfur element, nitrogen element and transition metal element.

6. The electrode active material according to claim 5, characterized in that The transition metal element includes at least one of nickel, cobalt, manganese, iron, chromium, titanium, vanadium, copper and zinc.

7. The electrode active material according to claim 5, characterized in that The chemical bonds contained in the electrode active material include at least one of a chemical bond between a transition metal atom and a sulfur atom, a chemical bond between a transition metal atom and a nitrogen atom, a chemical bond between a carbon atom and a nitrogen atom, and a chemical bond between a carbon atom and a sulfur atom.

8. An air battery, characterized in that: Including positive electrode sheet, negative electrode sheet and electrolyte; Wherein, the positive electrode sheet comprises a conductive agent, a binder and an electrode active material as described in any one of claims 1-7.

9. The air battery according to claim 8, characterized in that: The first coulombic efficiency of the air battery is in the range of 60%-89%; and / or, The 200-cycle capacity retention rate of the air battery is in the range of 60%-90%.

10. The air battery according to claim 8, characterized in that: The discharge gram capacity of the air battery is greater than or equal to 1400 mAh per gram.

11. A method for preparing an electrode active material, characterized in that: include: forming an electrode active material precursor; The electrode active material precursor is a porous material; A first oxygen-containing group is formed on the outer surface of the electrode active material precursor and the pore surface of the electrode active material precursor; the first oxygen-containing group is used to enhance the electrical activity of the electrode active material.

12. The method for preparing an electrode active material according to claim 11, characterized in that: The forming of the first oxygen-containing group comprises: Oxidizing the electrode active material precursor to form second oxygen-containing groups on the outer surface of the electrode active material precursor and the pore surface of the electrode active material precursor; The oxidized electrode active material precursor is heated by microwaves to convert at least a portion of the second oxygen-containing groups into the first oxygen-containing groups.

13. The method for preparing an electrode active material according to claim 12, characterized in that: The oxidant for oxidizing the electrode active material precursor is hydrogen peroxide; The mass ratio of the electrode active material precursor to the hydrogen peroxide is in the range of 1:10-1:

30.

14. The method for preparing an electrode active material according to claim 12, characterized in that: During the microwave heating of the oxidized electrode active material precursor, the microwave power ranges from 400 watts to 2000 watts; and / or, The microwave heating time of the oxidized electrode active material precursor is in the range of 10 seconds to 120 seconds.

15. The method for preparing an electrode active material according to any one of claims 12 to 14, characterized in that: The forming of the electrode active material precursor comprises: dissolving a carbon source and a nitrogen source in an acidic solution to obtain a first solution; adding a transition metal source and a sulfur source to the first solution to perform a hydrothermal reaction to obtain a first precipitate; The first precipitate is calcined in an inert gas atmosphere to obtain the electrode active material precursor.

16. The preparation method according to claim 15, characterized in that: The carbon source and the nitrogen source are biomass materials; The acidic solution includes at least one of a sulfuric acid solution, a hydrochloric acid solution, a nitric acid solution and an acetic acid solution; the concentration range of the acidic solution is 0.5%-15%.

17. The preparation method according to claim 16, characterized in that: The sulfur source includes at least one of thiourea and ammonium thioacetate; the mass ratio of the biomass material to the sulfur source is in the range of 1:0.01-1:

5.

18. The preparation method according to claim 16, characterized in that: The biomass material comprises at least one of wheat straw, rice straw, corn straw, wood chips, peanut shells, coconut shells, corn cobs, wheat bran, rice husks and coffee grounds.

19. The preparation method according to claim 17, characterized in that: The transition metal source is a transition metal sulfate; the mass ratio of the biomass material to the transition metal sulfate is in the range of 1:0.001-1:

8.

20. The method for preparing an electrode active material according to claim 16, characterized in that: The calcination temperature of the first precipitate is in the range of 600 degrees Celsius to 1200 degrees Celsius; and / or, The calcination time of the first precipitate ranges from 4 hours to 8 hours.

Citation Information

Patent Citations

  • Li-air battery negative electrode, Li-air battery and Li-air battery electrode preparation method

    CN104282918A